Bringing Mall beyond the Wall: Rethinking Online Learning Practices in Indonesian Higher Education - Purwaningrum, Adriani Yulia (English Language Education Department, Universitas Kristen Duta Wacana (UKDW), Yogyakarta, Indonesia, 2025)
MALL implementation in online learning practice has raised discussion on the possibility of developing learning beyond the classroom. However, online learning circumstances in Indonesia require special attention since this sudden shift of learning methods poses various challenges for teachers and students unfamiliar with this agenda. Therefore, this study reviews related and significant studies on online learning practice in Indonesian higher education. The selected samples were categorized and analyzed to understand the current circumstances of online learning in the Indonesian EFL context and examine the feasibility of learning beyond the classroom (LBC) to be developed in Indonesia. The results indicate that the online learning situation in Indonesia opens a wide opportunity for the development of LBC. Still, several aspects need further consideration and examination to achieve quality English language learning in an online environment. It is recommended for future researchers in the same field to further investigate LBC activities during online learning practice in Indonesia with the help of MALL.